Gruppenbild mit Dame: »Au juste poids véritable balance« (Amiens, 1518/19), Gerechtigkeitsﬁguration im Licht politischer Marienfrömmigkeit - Erk Volkmar Heyen (Rechtsgeschichte - Legal History)
The article explores a religious aspect of the genesis of the ﬁgure of ›Lady Justice‹ (with sword and scales), describing and interpreting a painting that owes its existence to a local literary association dedicated to the veneration of the Virgin Mary. The work, which shows a very large number of ﬁgures, reﬂects not only the religious but also the socio-economic and political interests of a town in the tense Franco-Dutch border region in the early 16th century. In its centre, Mary with infant Jesus sits enthroned between two scales. She is surrounded by, among others, King François I, Pope Leo X and Emperor Charles V. Contrary to the prevailing interpretation of the painting but in accordance with its titular motto, this article assigns the work to the European pictorial tradition of a ›weighing of souls‹, which – together with the archangel Michael – underlies the ﬁgural representation of ›Lady Justice‹. This also affects our interpretation of other aspects of the painting, so that, viewed as a whole, it expresses a connection between justice and mercy.